A novel hybrid approach of activated carbon and ultrasound cavitation for the intensification of palm oil mill effluent (POME) polishing. (20th January 2016) - Parthasarathy, Shridharan; Mohammed, Rafie Rushdy; Fong, Chong Mei; Gomes, Rachel L.; Manickam, Sivakumar
Abstract: This investigation focuses on activated carbon (AC) adsorption and ultrasound (US) cavitation for polishing the palm oil mill effluent (POME). Both AC adsorption and US cavitation were investigated individually, in series and operating them in a combined way. The efficiency of above processes has been evaluated in terms of removal of chemical oxygen demand (COD) and total suspended solids (TSS). For the individual operation, the optimisation studies were carried out by using the following conditions: AC dosage (50–200 g/L); contact time (2, 4, 6 h); US power amplitude (50% and 80%) and US cavitation time (30–180 min). The optimisation studies utilising US power amplitude (50%) and cavitation time (15 min) followed by AC adsorption using minimum AC dosage (50 g/L) and contact time (30 min) resulted in ∼100% COD and 83.33% TSS removals which meets the discharge limits set by the Department of Environment (DoE), Malaysia. The hybrid operation was also studied by simultaneously employing AC adsorption and US cavitation and it was observed that an adsorption dosage of 50 g/L resulted into achieving 73.08% COD and 98.33% TSS removals within 15 min of US irradiation. With the possibility of continuous and feasible sonochemical reactors, this hybrid approach of US cavitation followed by AC adsorption could be an alternative processing technique for POME polishing. Graphical abstract: Highlights: Biologically treated POME was further polished using a hybrid approach. Low frequency ultrasound system was utilised for POME polishing. US cavitation followed by AC adsorption led to higher COD removal. The treated effluent meets the discharge limits set by DoE. Promising green engineering technique for POME polishing.